Preoperative perforator localization in anterolateral thigh free flap using acoustic doppler and computed tomography angiography - Sungryeal Kim; Hye Ran Lee; Ju Hyun Yun; Jisun Yang; Jeon Yeob Jang; Yoo Seob Shin; Chul‐Ho Kim (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objectives Our aim in this study was to investigate if we could predict perforator localization during ALTF elevation, using information from acoustic Doppler (AD) and computed tomography angiography (CTA). Methods Prospective observational data were collected from H&N cancer patients who received reconstruction with ALTF in Ajou University Hospital Cancer Center from June to December, 2021. Total of 21 cases were included in the analysis. Lower extremity angio‐CT scans were used to determine the course and depth of the perforator before surgery. During intraoperative design of the ALTF, the possible location of the perforator was identified by AD. After flap elevation, the distance between the actual and Doppler‐identified location of the perforator was measured. Results The average distance from the actual location to the Doppler‐identified location was 1.29 ± 1.26 cm. Among 21 cases, almost all perforators (20 cases) were identified in a circle with a radius equivalent to the depth of the perforator. Perforator depth measured by CTA showed a significant positive correlation with the distance from the actual to Doppler‐identified location, regardless of skin thickness or body mass index (BMI). Conclusions A circle with a radius equivalent to the CTA‐assessed depth of the perforator successfully predicted the location of the perforator in almost all cases. Depth of the perforator measured by CTA combined with Doppler‐identified location can help safely locate the perforator during ALTF harvesting. Level of Evidence: 4.